2021
DOI: 10.3390/ijerph18020697
|View full text |Cite
|
Sign up to set email alerts
|

A Sequential Path Model Testing: Emotional Intelligence, Resilient Coping and Self-Esteem as Predictors of Depressive Symptoms during Unemployment

Abstract: The unemployment rate has dramatically increased in southern Europe in the last decade. Although it is well-known that unemployment impairs mental health, the specific roles of personal resources like emotional intelligence (EI) and potential underlying mechanisms remain unclear. Prior studies have shown that resilience and self-esteem are mediators in the link between EI and mental health. The present study aims to bridge these gaps by testing a sequential path model. Specifically, we propose that EI is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
3
10
0
1
Order By: Relevance
“…In regard to the first objective posed, and according to our first hypothesis, global self-esteem of physicians was found to be associated positively with the Stress Management and Adaptability dimensions of emotional intelligence, and especially with Mood, with which it has a close relationship. These results are similar to those found in other groups ( 47 , 48 ). Furthermore, studies such as the one by Pérez-Fuentes et al ( 45 ) have shown that mood is an important predictor of self-esteem in healthcare workers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In regard to the first objective posed, and according to our first hypothesis, global self-esteem of physicians was found to be associated positively with the Stress Management and Adaptability dimensions of emotional intelligence, and especially with Mood, with which it has a close relationship. These results are similar to those found in other groups ( 47 , 48 ). Furthermore, studies such as the one by Pérez-Fuentes et al ( 45 ) have shown that mood is an important predictor of self-esteem in healthcare workers.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the emotional intelligence of healthcare professionals has been found to be positively related to self-esteem ( 45 ), and more specifically, Mood is a strong predictor of it ( 46 ). These results are similar to those found in samples of other workers ( 47 ) and groups ( 48 ). Therefore, as emotions are based on implicit beliefs and their experience, expression and management are driven by sociocultural values ( 49 ), it is of interest to know these constructs in the Spanish medical context.…”
Section: Introductionsupporting
confidence: 91%
“…We used the Spanish version of Extremera et al (2019) , which has shown adequate validity and reliability in Spanish contexts (α = 0.91.). This instrument has been previously used in other studies in the Spanish context ( Peláez-Fernández et al, 2021 ; Yudes et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Table 1. The characteristics of the participants of the included articles [13,14,21,[27][28][29][30][31][32] No…”
Section: Self-esteem and Depression Among Participantsmentioning
confidence: 99%
“…According to past research, a moderate increase of self-esteem during adolescence is identified [25], which varies among individuals under different parenting styles [26], making it important for parents to receive advice on parenting styles to avoid harming self-esteem and increasing their risk of contracting depression. Also, it is shown that unemployed people have significantly lower self-esteem and higher depression than ordinary people [27]. This shows the need for the government to focus efforts on job losses, since it possibly gives rise to low self-esteem and psychological issues.…”
Section: Suggestionsmentioning
confidence: 99%